- 3

- 0

I am stuck on this problem. I can reach the correct answer with the quadratic formula, but not with the method suggested (completing the square). Thanks in advance.

The problem is:

[tex]2x^2+8x+1=0[/tex]

This is what I tried:

[tex]2x^2+8x=-1[/tex]

[tex]2(x^2+4x)=-1[/tex]

[tex]2(x^2+4x+4)=-1+8[/tex]

[tex]2(x+2)^2=7[/tex]

[tex](x+2)^2=\frac{7}{2}[/tex]

[tex]x=-2+\sqrt{\frac{7}{2}}[/tex]

The problem is:

[tex]2x^2+8x+1=0[/tex]

This is what I tried:

[tex]2x^2+8x=-1[/tex]

[tex]2(x^2+4x)=-1[/tex]

[tex]2(x^2+4x+4)=-1+8[/tex]

[tex]2(x+2)^2=7[/tex]

[tex](x+2)^2=\frac{7}{2}[/tex]

[tex]x=-2+\sqrt{\frac{7}{2}}[/tex]

Last edited: